Future Intentions of Fitness Center Customers: Effect of Emotions, Perceived Well-Being and Management Variables - García-Pascual, Fernando; Prado-Gascó, Vicente; Alguacil, Mario; Valantine, Irena; Calabuig-Moreno, Ferran (Frontiers in Psychology, 2020)
One of the main objectives of fitness center managers is to obtain high levels of loyalty from the customers of these fitness centers. Within the existing literature on fitness center management, previous research analyzed the importance of the management variables themselves in order to know the behavioral intentions of their customers. For this reason, this research tries to know, by means of different management variables, including also psychological and socio-demographic variables, what degree of prediction they have of the intentions of future behavior of the customers of these sports centers. To do so, two different methodologies are used to analyze all the variables. One of them is symmetric, such as hierarchical regressions, and the other one is asymmetric, such as fsQCA, which bases its analysis on a combination of sets. It is concluded how satisfaction and perceived value of customers variables predict more strongly future intentions, and how, psychological variables have more presence in low levels of future intentions. On the other hand, although they are two completely different methodologies, they are totally necessary and complementary in research related to the management of sports services.